2018
DOI: 10.1002/qj.3397
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and scale interactions in ocean ensembles: From seasonal forecasts to multidecadal climate predictions

Abstract: The ocean plays an important role in the climate system on time-scales of weeks to centuries. Despite improvements in ocean models, dynamical processes involving multiscale interactions remain poorly represented, leading to errors in forecasts. We present recent advances in understanding, quantifying, and representing physical and numerical sources of uncertainty in novel regional and global ocean ensembles at different horizontal resolutions. At coarse resolution, uncertainty in 21st century projections of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 87 publications
2
47
2
Order By: Relevance
“…We have shown that neural networks can successfully represent the spatiotemporal variability of the eddy momentum forcing, implying potential for data‐driven oceanic turbulence closures in the future, as suggested by Zanna et al (). The generalization ability of the neural networks shows that only a limited amount of observations or high‐resolution model data may be needed to successfully represent subgrid‐scale processes.…”
Section: Conclusion and Discussionsupporting
confidence: 64%
“…We have shown that neural networks can successfully represent the spatiotemporal variability of the eddy momentum forcing, implying potential for data‐driven oceanic turbulence closures in the future, as suggested by Zanna et al (). The generalization ability of the neural networks shows that only a limited amount of observations or high‐resolution model data may be needed to successfully represent subgrid‐scale processes.…”
Section: Conclusion and Discussionsupporting
confidence: 64%
“…This area has already been the subject of many observational studies (e.g., Line W, Toole et al (2011)) and is well observed by altimetry (see Lillibridge and Mariano (2013) and references within). Furthermore, initialisation of GCM ensemble simulations with the optimal initial conditions could provide a better estimate of initial condition uncertainty in SSH prediction (Zanna et al 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It also made use of a single model, and therefore the optimal initial conditions presented may be model specific. It would therefore be beneficial to examine the SSH predictability with a more extensive ensemble of model simulations, including those which isolate the effects of intrinsic processes (e.g., Sérazin et al (2015) and Zanna et al (2018)). Moreover, a comparison with altimetry or higher resolution model output may further elucidate the effects of the eddy field on interannual variability.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this Special Issue, Zanna et al . () discusses the state of the art in ocean modelling and recent advances in the design of ocean ensembles, and Xian et al . () raises issues linked to the prediction of aerosol.…”
Section: Discussionmentioning
confidence: 99%